2017
DOI: 10.1002/cphc.201700104
|View full text |Cite
|
Sign up to set email alerts
|

Performance of CuII‐, PbII‐, and HgII‐Exchanged Mordenite in the Adsorption of I2, ICH3, H2O, CO, ClCH3, and Cl2: A Density Functional Study

Abstract: Periodic dispersion-corrected DFT is used to investigate the adsorption of I and ICH , which may be released during a severe nuclear accident, for three divalent cation (Cu , Pb and Hg )-exchanged mordenites with an Si/Al ratio of 23. Gases such as H O, CO, ClCH , and Cl present in the containment atmosphere can inhibit the selective adsorption of iodine species. To identify the most promising adsorbents, a systematic study is performed in which all the possible cationic sites in the main channel of the morden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 52 publications
1
19
0
Order By: Relevance
“…[163][164][165][166][167][168] In the particular case of the capture of iodine species, the adsorption properties and cation exchange capacities of zeolites make them interesting and remarkable candidates for this application. In the literature, several zeolites of different structural types have been studied for the capture of iodine species, such as mordenite (MOR structural type), 29,34,74,76,77,79,80,[169][170][171][172][173][174][175][176][177][178] NaX and NaY zeolites (FAU type), 5,60,75,77,78,88,132,179 ZSM-5 (MFI type), 74,77 ferrierite (FER type) and zeolite beta (*BEA type) 74,77 (ESI, Table 3 †).…”
Section: Ag-exchanged Zeolitesmentioning
confidence: 99%
See 3 more Smart Citations
“…[163][164][165][166][167][168] In the particular case of the capture of iodine species, the adsorption properties and cation exchange capacities of zeolites make them interesting and remarkable candidates for this application. In the literature, several zeolites of different structural types have been studied for the capture of iodine species, such as mordenite (MOR structural type), 29,34,74,76,77,79,80,[169][170][171][172][173][174][175][176][177][178] NaX and NaY zeolites (FAU type), 5,60,75,77,78,88,132,179 ZSM-5 (MFI type), 74,77 ferrierite (FER type) and zeolite beta (*BEA type) 74,77 (ESI, Table 3 †).…”
Section: Ag-exchanged Zeolitesmentioning
confidence: 99%
“…Later, numerous studies were carried out on this topic, especially during the 1970s and 1980s 21,29,34,38,40,47,52,180 and then between 2000 and 2017. 5,8,71,[74][75][76][77][78][79][80][169][170][171][173][174][175][176][177][184][185][186][187][188] These studies focused on the determination of the inuence of various parameters such as the temperature ( C), silver content (wt%), Si/Al ratio, supercial velocity, and pretreatment of the material on the adsorption capacities of silver-exchanged zeolites (ESI, Table 3 †). Other works focused on issues such as aging of the material under different atmospheres (NO x , humidity).…”
Section: Ag-exchanged Zeolitesmentioning
confidence: 99%
See 2 more Smart Citations
“…In the case of zeolites, the ease of exchange reactions and the cation size are also further important criteria. Recently, some DFT studies conducted on different monovalent cationexchanged faujasite and mordenite have shown new insights for the adsorption of both I 2 and CH 3 I [21,22]. It was found that soft cations, such as Cu + and Ag + , are able to adsorb iodine compounds with high adsorption energies, even in presence of some inhibitors (apart from CO and to a lesser extent NO) potentially present under severe accidental conditions.…”
Section: Introductionmentioning
confidence: 99%